Temporal characteristics of child-adult conversations: utterances and turn-taking - Horváth, Viktória; Krepsz, Valeria (Taikomoji kalbotyra, 2023)
Since its inception, conversation analysis has focused on the question of how participants achieve a fast and smooth alignment between two turns. Most research has analyzed adults’ conversations, but much less has been known about child-adult interactions. The aim of this study is to analyze the temporal patterns of children’s utterances and turn-taking (TT). Twenty adult-child conversations (ages 5 and 7) were selected from the GABI database. Articulation rate, duration of interpausal units, pauses, and FTO-value (Floor Transfer Offset) of turn-taking launched by the children were analyzed. Temporal patterns did not differ between the two age groups, but individual differences were found within both groups. TT mostly occurred with a gap, but children were also able to take the floor immediately. TTs after a gap were significantly longer than after overlapping speech. The results provide new information on the communicative competence in childhood, particularly regarding timing patterns and organization of child-adult dialogues.